Migration of intrauterine device into the pelvic cavity: exploration strategy and management in African environment - Diouf, Abdoul Aziz; Diallo, Moussa; Gassama, Omar; Niang, Mouhamadou Mansour; Thiam, Mariétou; Gueye, Mamour; Mbaye, Magatte; Moreau, Jean Charles; Herendael, Bruno Van; Diouf, Alassane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
IUD migration is a rare complication. We report our experience in the treatment of five cases of uterine perforation and migration of IUDs. The average age of patients was 34.6 years, an average parity was 4. All patients felt an unusual pain during insertion of the IUD Tcu 380A. The location of the IUD was done through ultrasound and hysterography. Removal by laparoscopy was performed in all cases. The immediate impacts of the surgery were simple. Hysterography has its place in the location of the migrated IUD. Prevention is a good IUD insertion technique.